Dekonstrukcja nacjonalizmu w wybranych pracach Milicy Tomić - Aleksandra Czarny (Quart)
The paper discusses the artistic and conceptual strategies of the deconstruction of nationalism in the selected works of contemporary Serbian artist, Milica Tomić (b. 1960) by interpreting them from a hitherto overlooked perspective of Derridian deconstructivism. It demonstrates that the analyzed performances and billboards made by Tomić offer a consistent and theoretically self-aware attempt at a critical dismantling of the nationalist narratives present in post-Yugoslav public discourse through their emphasis on the constitutive function of national languages and state militarism. It is due to this deconstructivist framework that the particular experiences on which Tomić bases her art gain universal significance for our understanding of all nationalisms.